Navigating Complexity: Logistical Lessons from 15th-Century Maritime Explorations - Paché, Gilles (Archives of Business Research, 2025)
This article offers a fresh analysis of 15th-century maritime explorations through the lens of large-scale project management. By detailing the critical stages of these expeditions, from shipbuilding and recruitment to provisioning essential supplies, it highlights the ingenuity, meticulous planning, and organizational expertise of navigators in the face of extreme challenges. The author explores the efficient management of scarce resources, such as water and food, and examines how adaptability to unexpected events—storms, diseases, navigational errors, and equipment failures—enabled explorers to overcome the hardships of long ocean crossings. In a unique and thought-provoking manner, the article draws parallels between the logistical practices of 15th-century navigators and those used in managing complex 21st-century projects. This cross-disciplinary approach underscores the continued relevance of historical lessons for addressing modern logistical challenges, particularly in uncertain, volatile, and turbulent environments. Ultimately, the article stresses the importance of ethics in large-scale project management, reminding scholars that innovation and progress must prioritize human dignity, environmental sustainability, and long-term social responsibility.